Professional Emotions in Court A Sociological Perspective - Bergman Blix, Stina (Taylor & Francis, 2018)
Professional Emotions in Court examines the paramount role of emotions in the legal professions and in the functioning of the democratic judicial system. Based on extensive interview and observation data in Sweden, the authors highlight the silenced background emotions and the tacitly habituated emotion management in the daily work at courts and prosecution offices. Following participants 'backstage' - whether at the office or at lunch - in order to observe preparations for and reflections on the performance in court itself, this book sheds light on the emotionality of courtroom interactions, such as professional collaboration, negotiations, and challenges, with the analysis of micro-interactions being situated in the broader structural regime of the legal system - the emotive-cognitive judicial frame - throughout. A demonstration of the false dichotomy between emotion and reason that lies behind the assumption of a judicial system that operates rationally and without emotion, Professional Emotions in Court reveals how this assumption shapes professionals' perceptions and performance of their work, but hampers emotional reflexivity, and questions whether the judicial system might gain in legitimacy if the role of emotional processes were recognized and reflected upon.